2019
DOI: 10.1371/journal.pone.0221265
|View full text |Cite
|
Sign up to set email alerts
|

Screening for HBV, HCV, HIV and syphilis infections among bacteriologically confirmed tuberculosis prisoners: An urgent action required

Abstract: Viral hepatitis, syphilis, HIV, and tuberculosis infections in prisons have been identified globally as a public health problem. Tuberculosis (TB) and viral hepatitis co-infection may increase the risk of anti-tuberculosis treatment-induced hepatotoxicity, leading to the frequent cause of discontinuation of the first-line anti-tuberculosis drugs. Therefore, the aim of this cross-sectional study was to investigate the epidemiological features of HCV, HBV, syphilis and HIV infections among bacteriologically conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 36 publications
4
33
1
4
Order By: Relevance
“…This finding supports other similar findings suggesting that HIV co-infected TB patients have significantly lower cure rates and lower treatment success rates compared to non-HIV infected counterparts [25, 27, 37]. Viral co-infection might increase the risk of anti-tuberculosis treatment-induced hepatotoxicity leading to frequent discontinuation of the first-line anti-tuberculosis drugs and hence lower treatment adherence and lower cure rates [38].…”
Section: Discussionsupporting
confidence: 88%
“…This finding supports other similar findings suggesting that HIV co-infected TB patients have significantly lower cure rates and lower treatment success rates compared to non-HIV infected counterparts [25, 27, 37]. Viral co-infection might increase the risk of anti-tuberculosis treatment-induced hepatotoxicity leading to frequent discontinuation of the first-line anti-tuberculosis drugs and hence lower treatment adherence and lower cure rates [38].…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the rate of TB/HIV coinfection found (8.6 %) was consistent with previous studies conducted among prisoners in Brazil, where the rate varies between 6.8–18 %; however, this rate is less than the rate observed in the municipality (35.0 %) during the same study period [13, 27–29]. Moreover, coinfections of TB with HBV, HCV and syphilis, and the comorbidity TB/DM were not observed.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, coinfections of TB with HBV, HCV and syphilis, and the comorbidity TB/DM were not observed. However, rates of 1.4 % for TB/HBV coinfection, 4.7 % for TB/HCV coinfection, 5 % for TB/syphilis coinfection and 19 % for TB/DM comorbidities have been already reported in Brazilian prisons [29, 30]. Screening among prisoners may be responsible for the lower rates of these infections than in the general population [31].…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports other similar findings suggesting that HIV co-infected TB patients have significantly lower cure rates and lower treatment success rates compared to non-HIV infected counterparts [27,38,39]. Viral co-infection might increase the risk of anti-tuberculosis treatment-induced hepatotoxicity leading to frequent discontinuation of the first-line anti-tuberculosis drugs and hence lower treatment adherence and lower cure rates [40].…”
Section: Discussionsupporting
confidence: 89%